Histopathological and Clinical Features of Phyllodes Tumor in Hasan Sadikin during Period of 2012 - 2016 - Natasha A Harsas; Birgitta M Dewayani; Raden Yohana (Journal of Medicine and Health, 2018)
Phyllodes tumor is a breast fibroepithelial lesion that rarely occurred. This type of tumor has tendency to recurre and metastasize. This study aimed to determine the features of phyllodes tumor in Hasan Sadikin General Hospital in period of 2012 to 2016, histopathologically and clinically. Descriptive study with cross sectional design was conducted in Department of Pathological Anatomy, Hasan Sadikin General Hospital, Bandung, from September 2016 to May 2017. Using total sampling, the secondary data are taken from medical records with the diagnosis of phyllodes tumor. From 88 samples taken, the mean age of the tumor occurrence is 45,56 years old and the mean size of tumor diameter is 10,98 cm. Tumor with benign type has the highest prevalence, with 54 cases reported. Mastectomy is the most common procedure performed on this tumor. There are 7 recurred patients and 1 patient with metastasis. As conclusions, phyllodes tumor is a rare tumor. In Hasan Sadikin general hospital, it mostly occurs in women aged 45 years old in the benign type. Mastectomy is often performed as a choice of surgical treatment.